Pesquisa bibliográfica em revistas nacionais e internacionais sobre processos de formação de formadores e ensino de ciências - Dametto, Nicole Zanchetta (2019)
This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001 , part of the context of it of Institutions of Higher Education with quality in front of an information society. Several actions to guarantee this quality are already made worldwide, such as the creation of spaces for university teaching. In this sense, based on the assumption that teaching is a profession and as such it is learned, it had as objectives to identify which training proposals appear in published articles, identify which proposals insert Science Teaching and finally compare how they are treated at the national level and international. The bibliographical research resulted in 19 articles in the national scope and 21 articles in the international scope that were organized in three conceptions of learning (objectivist, constructivist and communicative). We can conclude that due to the few articles found and practically the absence of articles that deal with university teaching and Science Teaching that in Brazil is still a possible area for future research and publications, while in the international scope we have evidence of the possibility of more work about this theme.